Must global politics constrain democracy? : great-power realism, democratic peace, and democratic internationalism - Gilbert, Alan (Princeton University Press, 1999)
As each power vies for its national interests on the world stage, how do its own citizens' democratic interests fare at home? Alan Gilbert speaks to an issue at the heart of current international-relations debate. He contends that, in spite of neo-realists' assumptions, a vocal citizen democracy can and must have a role in global politics. Further, he shows that all the major versions of realism and neo-realism, if properly stated with a view of the national interest as a common good, surprisingly lead to democracy. His most striking example focuses on realist criticisms of the Vietnam War.